2017
DOI: 10.1159/000484623
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-Oxide Instigates NLRP3 Inflammasome Activation and Endothelial Dysfunction

Abstract: Background/Aim: Plasma trimethylamine-N-oxide (TMAO), a product of intestinal microbial metabolism of dietary phosphatidylcholine has been recently associated with atherosclerosis and increased risk of cardiovascular diseases (CVD) in rodents and humans. However, the molecular mechanisms of how TMAO induces atherosclerosis and CVD progression are still unclear. The present study tested whether TMAO induces NLRP3 inflammasome formation and activation and thereby contributes to endothelial injury initiating athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 60 publications
(61 reference statements)
5
158
0
Order By: Relevance
“…6,40,41 It also acts as a sensor to the damaging exogenous and endogenous elements and a switch on inflammatory and noninflammatory responses together. 42 Previous studies have established that ROS generation is the most common pathway in inflammasome assemblage, signing a possible connection between enhanced ROS production and inflammasome activation as Abais et al documented that inhibiting NADPH oxidase-derived ROS prohibited ATP-induced caspase-1 activation as well as IL-1β production. 43 Conversely, treatment with ROS inhibitors has been revealed to suppress silica/asbestosinduced NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…6,40,41 It also acts as a sensor to the damaging exogenous and endogenous elements and a switch on inflammatory and noninflammatory responses together. 42 Previous studies have established that ROS generation is the most common pathway in inflammasome assemblage, signing a possible connection between enhanced ROS production and inflammasome activation as Abais et al documented that inhibiting NADPH oxidase-derived ROS prohibited ATP-induced caspase-1 activation as well as IL-1β production. 43 Conversely, treatment with ROS inhibitors has been revealed to suppress silica/asbestosinduced NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 plays a protective role in age-related macular degeneration via the induction of IL-18 through drusen components [37]. In endothelial cells, the NLRP3 inflammasome exhibits a significant initiating mechanism, and its activation may accelerate the development of endothelial dysfunction or atherogenic pathology by inducing plasma trimethylamine-Noxide (TMAO) [38]. The repression of the NLRP3 inflammasome is a critical factor in I/R or inflammation by correlation with SIRT1, which was proved to be involved in both preventing cells from injury induced by various stress and improving endothelial precursor cell function [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence suggests that elevated serum TMAO levels are also linked to adipose tissue dysfunction and chronic kidney disease . Subsequent mechanistic studies identified the biologic function of TMAO to include endothelial dysfunction and enhancement of platelet hyperreactivity . Oral application of a structural analogue of choline, 3,3‐dimethyl‐1‐butanol, inhibited microbial TMA production, lowered serum TMAO levels, and prevented development of atherosclerotic lesions, despite a proatherosclerosis diet, in an animal model .…”
Section: Gut Microbial Metabolism and Interactions With The Human Hostmentioning
confidence: 99%
“…(98) Subsequent mechanistic studies identified the biologic function of TMAO to include endothelial dysfunction and enhancement of platelet hyperreactivity. (99,100) Oral application of a structural analogue of choline, 3,3-dimethyl-1-butanol, inhibited microbial TMA production, lowered serum TMAO levels, and prevented development of atherosclerotic lesions, despite a proatherosclerosis diet, in an animal model. (101) Together, these data support that a microbial-derived metabolite is an important contributor to a variety of interrelated cardiometabolic diseases and that targeting the gut microbial capacity to produce this metabolite offers a potential novel strategy for disease prevention or treatment.…”
Section: Gut Microbial Metabolism and Interactions With The Human Hostmentioning
confidence: 99%